Comparison of Two Measurement Devices for Pulse Wave Velocity in Children: Which Tool Is Useful to Detect Vascular Alterations Caused by Overweight? - Elmenhorst, Julia; Weberruss, Heidi; Mayr, Martina; Pfister, Karin; Oberhoffer, Renate (Frontiers in Pediatrics, 2019)
Vascular alterations may lead to manifest cardiovascular disease in future life. There is a tremendous time delay between the onset and obvious clinical appearance of vascular alterations. Pulse wave velocity (PWV) is one subclinical parameter to detect vascular alterations at a very early stage. Different techniques exist to measure PWV non-invasively as a vascular parameter—all with their own technique-inherent advantages, challenges, and pitfalls. The aim of this study was to compare two techniques to measure PWV, to assess their agreement, and interchangeability. In 780 (♀ = 49.4%) healthy children and adolescents (mean age: 11.61 ± 2.11 years), PWV was obtained with two different techniques. Ultrasound-measured local PWV (PWVβ) at the carotid artery was graphically compared by a Bland–Altman plot with aortic PWV (aPWV), measured oscillometrically on the brachial artery. Reproducibility was assessed with the concordance correlation coefficient by Lin (ρc). Furthermore, participants were categorized by BMI as normal weight (N) or overweight/obese (O) to identify differences in PWVβ and aPWV caused by an increased BMI. Mean PWVβ was lower (4.01 ± 0.44 m/s) than mean aPWV (4.67 ± 0.34 m/s). The two methods differ by mean Δ0.66 ± 0.47 m/s (95% CI: 0.62 to 0.69 m/s; p < 0.001). Bland–Altman analysis indicated the 95% limits of agreement (−0.26 to 1.57) without any evidence of systemic difference. Lin's ρc represented a weak concordance between PWVβ and aPWV (ρc = 0.122; 95% CI: 0.093–0.150). There was no difference in PWVβ between N and O, whereas aPWV was higher in O: 4.81 ± 0.42 m/s than in N: 4.65 ± 0.32 m/s (p < 0.001). The difference, Δ0.16 m/s, 95% CI [−0.25; −0.08], was significant, t(121) = −3.76, p < 0.001, with a medium-sized effect. PWVβ (ultrasound) and aPWV (oscillometry) show a level of disagreement that includes clinically important discrepancies. A discrimination between normal and altered vascular function was possible with aPWV but not with PWVβ.